2022
DOI: 10.1080/14756366.2022.2110869
|View full text |Cite
|
Sign up to set email alerts
|

New quinoline and isatin derivatives as apoptotic VEGFR-2 inhibitors: design, synthesis, anti-proliferative activity, docking, ADMET, toxicity, and MD simulation studies

Abstract: New quinoline and isatin derivatives having the main characteristics of VEGFR-2 inhibitors was synthesised. The antiproliferative effects of these compounds were estimated against A549, Caco-2, HepG2, and MDA-MB-231. Compounds 13 and 14 showed comparable activities with doxorubicin against the Caco-2 cells. These compounds strongly inhibited VEGFR-2 kinase activity. The cytotoxic activities were evaluated against Vero cells. Compound 7 showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Combining the molecules from two or more compound classes into a single molecule by chemical reactions is known as molecular hybridization. Molecular hybridization is a good drug design strategy [29] . Hybrid molecules obtained by combining molecules from two or more biologically active compound classes in a single molecule can be more effective and selective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining the molecules from two or more compound classes into a single molecule by chemical reactions is known as molecular hybridization. Molecular hybridization is a good drug design strategy [29] . Hybrid molecules obtained by combining molecules from two or more biologically active compound classes in a single molecule can be more effective and selective.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hybridization is a good drug design strategy. [29] Hybrid molecules obtained by combining molecules from two or more biologically active compound classes in a single molecule can be more effective and selective. The interest of chemists in the synthesis of new hybrid molecules continues to grow because of their biological and pharmaceutical properties.…”
Section: Introductionmentioning
confidence: 99%
“…After the FDA’s approval of the VEGFR-2 inhibitor Sunitinib, medicinal chemists have paid special attention to the identification of new isatin-based anti-cancer candidates targeting VEGFR-2 kinase [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Our research team has recently reported several VEGFR-2 inhibitors based on the isatin scaffold [ 45 , 46 , 47 , 48 , 49 , 50 ]. In 2020, we developed a new set of triazolo[3,4- b ]thiadiazine—isatin hybrids with promising anti-angiogenic activities [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compound I remarkably reduced the developed blood vessels; in addition, it was not toxic for the chick embryos. In the last year, another small set of 2,4-thiazolidindione—isatin hybrids with promising anticancer and VEGFR-2 inhibitory activities were reported [ 47 , 48 , 49 ]. Compound II ( Figure 1 ) revealed good anti-proliferative activities toward breast, lung, and colon cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of cytobiology and molecular biology, the essential principles of tumorigenesis, invasion, migration, and metastasis induced by quinoline derivatives have been further explained. Antitumor mechanisms of quinoline derivatives include alkylating DNA [ 14 ], inhibiting c-Met kinase [ 15 ], epidermal growth factor receptor (EGFR) [ 16 ], and vascular endothelial growth factor (VEGF) [ 16 , 17 , 18 ]. Some were also proven to inhibit P-glycoprotein [ 19 ].…”
Section: Introductionmentioning
confidence: 99%